SYNTHESIS OF KINEMATIC CONTROL OF AN AIRCRAFT IN ”BIG” - Pavlova, Svetlana (Proceedings of National Aviation University (archive), 2014)
In the article the application reconfiguration technology for the decision of a problem of difficult nonlinear object control in the greatest possible area of its states is shown.